Adjusting external calibration intervals for auxiliary devices in testing laboratories according to intermediate checks results. Issue 1 (1st January 2021) - Gaber, Seleem E.
ABSTRACT: An unfortunate thing which is not desirable to happen in testing laboratories is that after working for weeks on tests, it is discovered that one of the used equipment is not accurate. Therefore, intermediate checking these devices from time to time is a reasonable way to reduce the risk of errors in laboratory work. The Central Laboratory for Environmental Quality Monitoring (CLEQM) performs intermediate check for testing equipment, besides the annual calibration done by an accredited body, to maintain confidence in its accuracy and precision between calibration intervals. This paper discusses the laboratory procedures to perform intermediate checks for electronic balances and micropipettes to comply with ISO/IEC:17025 requirements in the field of water quality testing. Intermediate check for balances was carried out according to OIML R111-2004 (E), while intermediate check for micropipettes was performed according to ISO 8655-6-2002 . The results of intermediate checks and control charts were used to monitor equipment needs for recalibration. The results indicated that calibration of laboratory equipment is not necessarily neither to be annually nor at fixed time intervals. However, it should be based on the drift in measurements, which can be detected through regular intermediate check. Where results are tracked through control charts and in case that, it is drifted out of control limits, a nonconformance is reported, and appropriate corrective actions are taken including calibration if required. It is concluded that calibration of supporting equipment according to their intermediate check is more favorable than fixed time intervals due to the high degree of reliability of the generated test results in addition to reduced financial costs, which is expected to be 25% to 40% lower than the cost of calibration with fixed intervals.